Teachers' Personal Page in a Social Network as a Tool for Teacher-Student Interaction - A. G. Kukushkina (Moscow Polytechnic University, 2020)
The article presents an analysis of the pedagogical capabilities of social networks in solving modern educational problems. The pedagogical potential of teacher's personal page can influence on individualization of the educational process, selection of the content of education, organization of pedagogical communication, involvement in activities. The author describes and analyzes the experience of interacting with students on the social network platform, which confirms the positive impact of the communication with the teacher through a social network on students' attitude to the subject and educational motivation. The restrictions of the use of teachers' personal pages in the process of education are connected with increased requirements to the content and design of a personal page. Possible negative consequences of interacting with students through social networks include non-compliance with the boundaries and blurring the boundaries of communication, the interpenetration of professional and personal spheres of life.